Influence of behavioral factors on mobile phone usage among fishermen: the case of Pangkor Island fishermen - Ramli, Siti Aisyah; Omar, Siti Zobidah; Bolong, Jusang; Alby, Jeffrey Lawrence D'Silva; Mohamed Shaffril, Hayrol Azril (Canadian Center of Science and Education, 2013)
The swift evolution of mobile phone technology has benefited various groups within communities. Fishermen, as one of the important groups, particularly in terms of their role in ensuring the nation’s food security, rely on mobile phones to conduct their fishing routines. While there is an abundance of studies that explore factors influencing mobile phone usage in various groups of communities, less interest has been placed on mobile phone usage among fishermen. This has driven the current study to its focal objective, which is to determine the behavioral factors that influence the usage of mobile phones among fishermen. This study is quantitative, and surveys a total of 250 registered fishermen from Pangkor Island – one of the main fishing areas in Perak. The results demonstrate that most of the fishermen use mobile phones for safety and communication purposes. In addition, due to a number of problems, fishermen are found to use advanced mobile phone applications such as 3G, Internet and GPS at a minimal level. Further analysis confirms that four behavioral factors, namely performance expectancy, effort expectancy, behavioral intention and social influence, have positive and significant correlations with mobile phone usage.